2019
DOI: 10.1002/mabi.201900021
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bone Defect Repair by Polymeric Substitute Fillers of MultiArm Polyethylene Glycol‐Crosslinked Hyaluronic Acid Hydrogels

Abstract: Bone regeneration is still one of the greatest challenges for the treatment of bone defects since no current clinical approach has been proven effective. To develop an alternative biodegradable bone graft material, multiarm polyethylene glycol (PEG) crosslinked hyaluronic acid (HA) hydrogels are synthesized and applied to promote osteogenesis of mesenchymal stem cells (MSCs) with the ultimate goal for bone defect repair. The multiarm PEG‐HA hydrogels provide a significant improvement of alkaline phosphatase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Although many studies have shown that HA holds great potential for promoting osteogenesis in vitro ( Koca et al, 2019 ; Yuan et al, 2019 ; Jang et al, 2020 ), recent findings have demonstrated that HA serves more as an osteoinductive scaffold since application of HA alone failed to induce sufficient bone regeneration as compared to treatments involving graft materials ( Sindel et al, 2017 ; Diker et al, 2018 ). Similarly, the presence of HA alone in the implant osteotomy also failed to yield improved osseointegration ( Yazan et al, 2019 ).…”
Section: Proteoglycans Modulate the Chondrogenic Differentiation Of Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have shown that HA holds great potential for promoting osteogenesis in vitro ( Koca et al, 2019 ; Yuan et al, 2019 ; Jang et al, 2020 ), recent findings have demonstrated that HA serves more as an osteoinductive scaffold since application of HA alone failed to induce sufficient bone regeneration as compared to treatments involving graft materials ( Sindel et al, 2017 ; Diker et al, 2018 ). Similarly, the presence of HA alone in the implant osteotomy also failed to yield improved osseointegration ( Yazan et al, 2019 ).…”
Section: Proteoglycans Modulate the Chondrogenic Differentiation Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…This suggested that HA alone was insufficient for bone regeneration, therefore the combination of HA and other material such as collagen and hydroxyapatite may be essential for improving bone regeneration in vivo . Yuan et al (2019) developed a bio-degradable bone graft material consisting of multiarm polyethylene glycol crosslinked with HA hydrogels, which brought a significant improvement to ALP activity and calcium mineralization in vitro . The multiarm PEG-HA hydrogels also facilitated healing of the cranial bone defects of rats.…”
Section: Proteoglycans Modulate the Chondrogenic Differentiation Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Because the cells are not able to adhere directly to it, recent studies have used combinations of natural compounds such as hyaluronic acid (HA) or gelatin, thus optimizing their characteristics (Sharma et al, 2015;D'souza and Shegokar, 2016). However, synthetic biomaterials have a limited capacity to induce endogenous repair responses, so their majority use has been for prostheses and implants (Koupaei et al, 2015;Yuan et al, 2019).…”
Section: Composition Syntheticmentioning
confidence: 99%
“…Finally, the results showed that the HA-TA-PL hydrogel induced the formation and deposition of cartilage-like extracellular matrix. Also, to enhance the osteogenesis of MSCs, Jishan Yuan et al used hydrogels based on the multiarm polyethylene glycol (PEG) cross-linked with hyaluronic acid (HA) (PEG-HA hydrogels) [98]. Synthesis of three types of the HA-based hydrogels through Michael addition reaction between a thiol group of crosslinkers and methacrylate groups on HA is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Republished with permission of ref. [98], Yuan J, Maturavongsadit P, Metavarayuth K, Luckanagul JA, Wang Q. Enhanced Bone Defect Repair by Polymeric Substitute Fillers of MultiArm Polyethylene Glycol-Crosslinked Hyaluronic Acid Hydrogels.…”
Section: Introductionmentioning
confidence: 99%